Mineral Components In Different Varieties Of Sweet Potato - Nozima Ismailova (Zien Journals, 2024)
This article contains information on the amount of macro and micronutrients in the leaves of sweet potato varieties. Khazina, Khazina 2, Khazina 3, Khazina 4 and GulDU varieties of sweet potatoes were selected as the object of research. The amount of nitrate form of nitrogen in sweet potato leaves is 4.03, phosphorus - 53.2 per 100 g. potassium -44.1 mg, iron -19.8, molybdenum -56.3, sulfate -93.1, boron -0.9, zinc -0.43, chlorine (mg/l) - 19.9 and copper 1.80 mg. It was noted that the majority of microelements was sulfate ion. It was found that the new varieties Khazina-2 and Khazina 4 of Batat differed in the amount of macro and micronutrients compared to other varieties.
Keywords: micro and macro elements; sweet potato plant; sweet potato varieties